Prior appropriation and water planning reform in Montana's Yellowstone River Basin: path dependency or boundary object?. Issue 2 (4th March 2018) - Anderson, Matthew B.; Ward, Lucas C.; Gilbertz, Susan J.; McEvoy, Jamie; Hall, Damon M.
ABSTRACT: This study deepens our understanding of the institutional limitations of participatory water planning. Based on an analysis of a participatory planning effort in Montana, U.S.A., we examine the ways in which prior appropriation (PA), an established legal doctrine based on privatized water rights, both constrains and enables the effective functioning of this mode of governance to enhance water conservation practices. In one situation, a state-led proposal to require water-use measuring was undermined by strong libertarian resistance to governmental regulation. As an expression of path dependency, PA redirected the deliberations back to the status-quo. Yet, in another state-led proposal, PA functioned as a boundary object that helped garner consensual support for what is effectively an alternative water sharing plan based on 'shared sacrifice.' In this second case, PA functioned as a pragmatic means to facilitate conservation practices to address future projections of growing water scarcity and drought. The study empirically examines the discursive framework of both policy recommendations and the mechanisms that led to their seemingly divergent receptions from planning participants. Evidence is drawn from a systematic content analysis of video recording transcriptions, ethnographic notes taken during meetings, and key interactions observed among planning participants and the research team.